20.0k views
3 votes
Сатре о

Find the condition that the roots of the quadratic equation
ax2 + cx + C =0
may be in the ratio m:n​

User Jobo
by
5.3k points

1 Answer

4 votes

Answer:


mnb^2 = ac(m+n)^2

Explanation:

Given


ax^2 +bx + c = 0

Required

Condition that the roots is in m : n

Let the roots of the equation be represented as: mA and nA

A quadratic equation has the form:


x^2 + (sum\ of\ roots)x + (product\ of\ roots)=0

or


x^2 - ((b)/(a))x + (c)/(a) = 0

We have the roots to be mA and nA.

So, the sum is represented as:


Sum = mA + nA


Sum = A(m + n)

And the product is represented as:


Product = mA * nA


Product = mnA^2

By comparing:


x^2 + (sum\ of\ roots)x + (product\ of\ roots)=0

with


x^2 - ((b)/(a))x + (c)/(a) = 0


Sum = -(b)/(a)


Product = (c)/(a)

So, we have:


Sum = -(b)/(a)


A(m + n) = -(b)/(a)

Make A the subject:


A = (-b)/(a(m+n))


Product = (c)/(a)


mnA^2 = (c)/(a)

Substitute
A = (-b)/(a(m+n))


mn((-b)/(a(m+n)))^2 = (c)/(a)


mn(b^2)/(a^2(m+n)^2) = (c)/(a)

Multiply both sides by a


a * mn(b^2)/(a^2(m+n)^2) = (c)/(a) * a


(mnb^2)/(a(m+n)^2) = c

Cross Multiply:


mnb^2 = ac(m+n)^2

Hence, the condition that the ratio is in m:n is


mnb^2 = ac(m+n)^2

User MaxPY
by
5.2k points